Оптимізація технології та виявлення фальсифікації пряжених молочних продуктів з використанням інструментальних сенсорних аналізаторів - Логінова, Анна Олегівна (My University, 2026)
Дисертацію присвячено оптимізації технології та виявленню фальсифікації пряжених молочних продуктів з використанням інструментальних сенсорних аналізаторів (ручного колориметра та системи «електронний ніс»). Пряжені молочні продукти (пряжене молоко, ряжанка) займають важливе місце у структурі споживання молочної продукції, завдяки характерному кремово-карамельному кольору та специфічному аромату, що формуються під час тривалого термічного оброблення молока. Водночас, традиційна технологія пряження характеризується значною енергоємністю, тривалістю процесу та високою варіабельністю якості готового продукту. На практиці контроль ступеня пряження здебільшого здійснюється органолептично, що зумовлює суб’єктивність оцінювання та ускладнює стандартизацію виробництва. Необхідним є розроблення об’єктивних інструментальних методів контролю процесу пряження молока для оптимізації процесу виробництва та забезпечення стабільної якості готової продукції. Крім того, зростання випадків фальсифікації пряжених молочних продуктів внесенням барвників і ароматизаторів потребує об’єктивних інструментальних методів виявлення фальсифікації. У роботі проаналізовано сучасні наукові підходи до застосування колориметричних показників для оцінювання інтенсивності термічного оброблення молока. На основі порівняльного аналізу колориметричних систем CIELab, CIEXYZ та CIERGB. Для подальшої роботи було обрано систему CIELab. Саме вона, разом із індексами білизни та пряження, виявилася найбільш чутливою до змін, що відбуваються під час термічного оброблення молока. 3 Встановлено, що використання інструментальних сенсорних аналізаторів дає змогу прогнозувати органолептичні властивості продукту вже з початку технологічного циклу. Дослідженнями змін параметрів L*, a*, b* та ΔE встановлено чіткі закономірності формування кольору пряженого молока. Визначено еталонні характеристики готового продукту: світлота L* = 79…86 од., координата червоного спектра a* = 2…4 од. та жовтого b* = 12...16 од. Ці цифри є об’єктивним критерієм завершення процесу пряження молока для молокасировини з масовою часткою жиру 4,0 % та вхідними колірними характеристиками: L*=84,0±1,6 од., a*= – 4,3±0,05 од., b*= 1,6±0,07 од. та колірною різницею: ΔE=12,0, достатньо пряжити молоко 205 хв. Розроблено математичні моделі, що дозволяють прогнозувати тривалість пряження залежно від вхідних параметрів сировини. Зокрема, доведено, що молоко жирністю 4,0% із початковою колірною різницею ΔE=12,0 достатньо пряжити протягом 205 хвилин для досягнення оптимальних показників якості. Це дозволяє відійти від жорстких часових регламентів і розрахувати тривалість пряження конкретної партії сировини для забезпечення стабільної якості продукції, навіть за умов сезонної мінливості складу молока та варіативності його жирності. Для практичної реалізації розроблено та затверджено «Методику вимірювання кольору пряжених молочних продуктів у системі CIE L*a*b* з використанням ручного колориметра LS173». Це створює інструментальну базу для впровадження результатів роботи на будь-якому підприємстві галузі. Сформовано практичні рекомендації у вигляді двох алгоритмів: контролю процесу пряження та контролю процесу сквашування пряженого молока. Ці алгоритми впроваджено у виробничу діяльність ПП «Білоцерківська агропромислова група». Економічний ефект від реалізації запропонованих рішень зумовлений зниженням енерговитрат. Оптимізація часу пряження дозволяє зменшити собівартість однієї тонни продукції для пряженого молока – на 456,25 грн, для ряжанки – на 546,38 грн. (в умовах ПП «Білоцерківська агропромислова група»). 4 Дисертація пропонує вирішення проблеми забезпечення стабільної якості пряжених молочних продуктів та оптимізацію тривалості їх виробництва, поєднуючи математичну точність моделювання з практичною ефективністю сенсорних аналізаторів. Важливим результатом роботи є розроблення схеми виявлення фальсифікації пряжених молочних продуктів. Спільне використання ручного колориметра та системи «електронний ніс» дозволяє за допомогою кластерного аналізу швидко і достовірно відрізнити натуральний продукт від підробок, що містять барвники або ароматизатори. Достовірність отриманих результатів підтверджено використанням сучасних методик досліджень, відповідного обладнання, використанням математичних засобів для опрацювання результатів. Наукові положення та рекомендації підтверджені лабораторними дослідженнями, проведеними в лабораторіях Національного університету харчових технологій. The dissertation is devoted to the optimisation of technology and the detection of counterfeit fermented milk products using instrumental sensory analysers (handheld colorimeter and «electronic nose» system). Fermented milk products (fermented milk, ryazhenka) occupy an important place in the structure of dairy product consumption due to their characteristic creamy caramel colour and specific aroma, which are formed during prolonged heat treatment of milk. At the same time, traditional baking technology is characterised by significant energy consumption, the length of the process and high variability in the quality of the finished product. In practice, the degree of baking is mostly controlled organoleptically, which leads to subjectivity in assessment and complicates the standardisation of production. It is necessary to develop objective instrumental methods for controlling the milk boiling process in order to optimise the production process and ensure the stable quality of the finished product. In addition, the increase in cases of falsification of boiled milk products by adding colourings and flavourings requires objective instrumental methods for detecting falsification. The paper analyses modern scientific approaches to the use of colorimetric indicators for assessing the intensity of milk heat treatment. Based on a comparative analysis of the CIELab, CIEXYZ and CIERGB colorimetric systems, the CIELab system was selected for further work. It, together with the whiteness and yoghurt indices, proved to be the most sensitive to changes occurring during the heat treatment of milk. 9 It has been established that the use of instrumental sensory analysers makes it possible to predict the organoleptic properties of the product from the very beginning of the technological cycle. Studies of changes in the parameters L*, a*, b* and ΔE have established clear patterns in the colour formation of curdled milk. The reference characteristics of the finished product have been determined: lightness L* = 79...86 units, red spectrum coordinate a* = 2...4 units and yellow b* = 12...16 units. These figures are an objective criterion for completing the milk coagulation process for raw milk with a fat content of 4.0% and the following initial colour characteristics: L*=84,0±1,6 units, a*= – 4,3±0,05 units, b*= 1,6±0,07 units and colour difference: ΔE=12,0, it is sufficient to pasteurise the milk for 205 minutes. Mathematical models have been developed that allow predicting the duration of curdling depending on the input parameters of the raw material. In particular, it has been proven that milk with a fat content of 4.0% and an initial colour difference of ΔE=12.0 needs to be curdled for 205 minutes to achieve optimal quality indicators. This allows us to move away from strict time regulations and calculate the duration of curdling for a specific batch of raw materials to ensure stable product quality, even under conditions of seasonal variability in milk composition and fat content. For practical implementation, the ‘Methodology for measuring the colour of fermented milk products in the CIE L*a*b* system using the LS173 handheld colorimeter’ has been developed and approved. This creates an instrumental basis for the implementation of the results of the work at any enterprise in the industry. Practical recommendations have been formulated in the form of two algorithms: control of the curdling process and control of the fermentation process of curdled milk. These algorithms have been implemented in the production activities of the Bilotserkivka Agroindustrial Group, Private Enterprise. The economic effect of the implementation of the proposed solutions is due to a reduction in energy costs. Optimisation of the curdling time allows reducing the cost of one tonne of curdled milk by 456,25 UAH and of ryazhenka by 546,38 UAH (under the conditions of the Bilotserkivka Agroindustrial Group, Private Enterprise). The dissertation proposes a solution to the problem of ensuring the stable quality of fermented milk products and optimising the duration of their production, combining 10 the mathematical accuracy of modelling with the practical efficiency of sensory analysers. An important result of the work is the development of a scheme for detecting counterfeit fermented milk products. The combined use of a handheld colorimeter and an «electronic nose» system allows, with the help of cluster analysis, to quickly and reliably distinguish natural products from counterfeits containing dyes or flavourings. The reliability of the results obtained is confirmed by the use of modern research methods, appropriate equipment, and mathematical tools for processing the results. The scientific positions and recommendations are confirmed by laboratory studies conducted in the laboratories of the National University of Food Technologies.
Keywords: колориметрія; пряжене молоко; ряжанка; фальсифікація; електронний ніс; ферментовані молочні продукти; сенсорний аналіз; показники якості; quality indicators; quality indicators; Maillard reaction; Maillard reaction; heat treatment; colorimetry; baked milk; fermented baked milk; counterfeiting; electronic nose; fermented milk products; sensory analysis